Improving Earthquake Reduction Methods - Djuraev, S. M. (European Journal of Life Safety and Stability (2660-9630), 2022)
This article is about construction in the modern world. And the seismic and fire safety of facilities is one of the most important issues; the losses and consequences of strong earthquakes are analyzed in detail. In the 21st century, there is an increase in seismic activity on the planet, in this regard; the speech is going on that there is a need to improve the development of new types of passive and active seismic protection systems to prevent unexpected earthquakes and fires.